2019
DOI: 10.1111/nuf.12352
|View full text |Cite
|
Sign up to set email alerts
|

Nursing student perceptions of hope in children: A qualitative descriptive study

Abstract: Hope has been linked to positive health outcomes in the literature. Hope is abstract, multidimensional, future-oriented, and occurs cognitively making it difficult to assess in children. Most of the research on hope has been conducted with adults and adolescents. Therefore, it is essential to analyze the concept of hope in children to provide nurses with tools to identify hope behaviors in children. The aim of this qualitative descriptive study was to describe hope behaviors in children from a nursing student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…From the point of view of psychology, hope may be related to resilience ( 13 ) . However, as it is a complex concept, there is no common definition to be applied universally ( 9 , 14 ) . In the pediatric context, recently a thematic synthesis of qualitative studies identified the experience of hope in families living with pediatric chronic illness ( 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of psychology, hope may be related to resilience ( 13 ) . However, as it is a complex concept, there is no common definition to be applied universally ( 9 , 14 ) . In the pediatric context, recently a thematic synthesis of qualitative studies identified the experience of hope in families living with pediatric chronic illness ( 15 ) .…”
Section: Introductionmentioning
confidence: 99%